Why is ASEAN not intrusive? Non-interference meets state strength. Issue 2 (3rd July 2019) - Suzuki, Sanae
ABSTRACT: Background: ASEAN is characterized as a non-intrusive regional organization. It has been argued that noninterference principle was prioritized over democracy and human rights because of undemocratic regimes in some member states and the success of its "ASEAN Way" of diplomacy. Purpose: This article demonstrates that such arguments, although dominant in the literature, struggle to explain the ASEAN experience. It will argue that, fundamentally, ASEAN remains non-intrusive because its member states share an understanding that domestic issues should be managed domestically, since the members have sufficient capability to do so. This common understanding enables each of them to avoid relying on ASEAN institutions. Main Argument: Taking non-traditional security issues as cases, this article argues that the noninterference principle has been maintained via this shared understanding. This argument might seem to be inconsistent with the moments when member states sometimes advocate for an intrusive ASEAN. It is not. Rather, such requests are made when doing so is line with the states' own interests, but such advocacy does not lead to changes in the basic ASEAN approach because the members retain their shared understanding that domestic issues should be managed domestically. Conclusion: Members facing a domestic challenge with potential spillover effects persuade the organization that they have enough state strength to manage the challenge internally. All members are ready to be persuaded from their shared understanding that they can rely on state strength to solve domestic issues. To date, however, members have successfully convinced one another that domestic capabilities are sufficient to address the issues under discussion.